Designing an Electronic Training Environment Based on Theory of Mind and its Impact on Improving the Executive Functions of Students with Autism Spectrum Disorder - Abdelraouf Mohamed Ismail; Noura bint Awadha Abdullah Al-Harbi (International Journal of Computers and Informatics, 2025)
This study aimed to measure the effect of designing an electronic training environment based on the theory of mind on improving the level of executive functions for students with autism spectrum disorder by identifying the appropriate executive functions for them, identifying the appropriate educational design for that environment, and measuring its effect on improving the level of executive functions in those students. The study adopted the quasi-experimental approach with a single-group experimental design in the pre- and post-applications. The study population consisted of students with autism spectrum disorder enrolled in a development center in Riyadh. The study sample consisted of (5) students who were selected intentionally based on the convergence of their scores on the Binet Intelligence Scale and the Gilliam Autism Severity Scale so that they would be within the category of those with autism spectrum disorder to a mild degree and with normal intelligence scores between 85-115 on the Stanford-Binet scale, and their ages ranged between 8-14 years. The researcher used a scale for executive functions for children with autism spectrum disorder prepared by Mustafa Aref (2020) and standardized it in the Saudi environment. The study reached a number of results, the most prominent of which are: There is a very significant effect of using the electronic training environment based on the theory of mind on improving the level of all executive functions among these students, as there are statistically significant differences at the significance level (0.05) between the average ranks of the sample members in the pre- and post-application of the executive functions scale in favor of the post-application. Therefore, the study recommended expanding the scope of using electronic training environments based on the theory of mind in teaching students with autism spectrum disorder; given the proven positive effect on developing the level of their executive functions.
Keywords: E-Learning Environment; Theory of Mind; Executive Functions; Students with Autism Spectrum Disorder